PEDIATRIC MORTALITY AT THE MOSCOW IMPERIAL ORPHANAGE: REALITY AND MYTHS - S. A. Sher; A. A. Baranov; V. Y. Albitskiy (Union of pediatricians of Russia, 2014)
The article is dedicated to the issue of pediatric mortality at the Moscow Imperial Orphanage founded on September 1, 1763, by decree of Empress Catherine II. The authors present results of an analysis of medical statistical data and give an objective assessment of the medical service provided by the Moscow Orphanage in order to understand the positive or the negative role of the Orphanage in the preservation of children's lives. The stated data do not confirm a myth of the Orphanage being a "factory of angels". Despite high pediatric mortality observed in the active period of the Moscow Imperial Orphanage, the doctors succeeded in saving hundreds of thousands of the children left for dead. The care of poor infants and preservation of their lives played an important role in the development of medical care and social welfare of the pediatric population of Russia.